Proteomic profile response of Paracoccidioides lutzii to the antifungal argentilactone - Prado, Renata S.; Bailão, Alexandre M.; Silva, Lívia C.; de Oliveira, Cecília M. A.; Marques, Monique F.; Silva, Luciano P.; Silveira-Lacerda, Elisângela P.; Lima, Aliny P.; Soares, Célia M.; Pereira, Maristela (Frontiers in Microbiology, 2015)
The dimorphic fungi Paracoccidioides spp. are the etiological agents of paracoccidioidomycosis (PCM), a mycosis of high incidence in Brazil. The toxicity of drug treatment and the emergence of resistant organisms have led to research for new candidates for drugs. In this study, we demonstrate that the natural product argentilactone was not cytotoxic or genotoxic to MRC5 cells at the IC50 concentration to the fungus. We also verified the proteomic profile of Paracoccidioides lutzii after incubation with argentilactone using a label free quantitative proteome nanoUPLC-MSE. The results of this study indicated that the fungus has a global metabolic adaptation in the presence of argentilactone. Enzymes of important pathways, such as glycolysis, the Krebs cycle and the glyoxylate cycle, were repressed, which drove the metabolism to the methylcytrate cycle and beta-oxidation. Proteins involved in cell rescue, defense and stress response were induced. In this study, alternative metabolic pathways adopted by the fungi were elucidated, helping to elucidate the course of action of the compound studied.